Characterization of homoserine dehydrogenase from Saccharomyces cerevisiae: An antifungal target - Jacques, Lyne Suzanne (My University, 1999)
Homoserine dehydrogenase (HSD), the third enzyme in the aspartate biosynthetic pathway producing isoleucine, methionine and threonine, is an important new antifungal target. Previously, (S )-2-amino-4-oxo-5-hydroxypentanoic acid (RI-331), an antifungal compound, demonstrated inhibitory activity against HSD from Saccharomyces cerevisiae . This pathway is an excellent target for the development of new non-toxic antifungal drugs, as it is absent in mammals. In order to design effective inhibitors of fungal HSD, a full kinetic and mechanistic characterization of this enzyme was required. Consequently, HSD from a model fungus, S. cerevisiae , was examined. Surprisingly, yeast HSD was able to bind either cofactor, NADPH or NADH, with high affinity. Product inhibition studies suggested that yeast HSD preferentially binds the nicotinamide cofactor before the amino acid substrate and releases the cofactor last. The inhibition pattern of the newly discovered HSD inhibitor, H-(1,2,4-triazol-3-yl)- D,L -alanine, was consistent with the proposed substrate binding order. In addition, viscosity and kinetic isotope experiments provided evidence for a fast catalytic step and a rate-limiting NAD(P)+ release during HSD catalysis. The stereochemistry of hydride transfer was determined to be from the pro-S C-4 nicotinamide hydrogen by kinetic isotope effects. Chemical modification experiments and site-directed mutagenesis of HSD determined that histidine 309 is an important residue in HSD catalysis. However, the recently solved HSD X-ray structure revealed that His309 may, in fact, be solely important in HSD dimerization. On the other hand, pH studies demonstrated that basic residues are involved primarily in substrate binding, in agreement with lysine residues discovered in the active site of the HSD structure. Lastly, RI-331 demonstrated many properties of a mechanism-based inactivator. This compound appears to form an adduct with NAD(P)+ in an HSD-dependent manner, thereby producing a tight-binding transition-state analog of yeast HSD. These studies will provide the necessary foundation for the development of a new class of antifungal drugs targeting amino acid biosynthesis.
Keywords: Biochemistry; Biochemistry